Debaryomyces hansenii Strains Isolated From Danish Cheese Brines Act as Biocontrol Agents to Inhibit Germination and Growth of Contaminating Molds - Huang, Chuchu; Zhang, Ling; Johansen, Pernille Greve; Petersen, Mikael Agerlin; Arneborg, Nils; Jespersen, Lene (Frontiers in Microbiology, 2021)
The antagonistic activities of native Debaryomyces hansenii strains isolated from Danish cheese brines were evaluated against contaminating molds in the dairy industry. Determination of chromosome polymorphism by use of pulsed-field gel electrophoresis (PFGE) revealed a huge genetic heterogeneity among the D. hansenii strains, which was reflected in intra-species variation at the phenotypic level. 11 D. hansenii strains were tested for their ability to inhibit germination and growth of contaminating molds, frequently occurring at Danish dairies i.e. Cladosporium inversicolor, Cladosporium sinuosum, Fusarium avenaceum, Mucor racemosus, and Penicillium roqueforti. Especially the germination of C. inversicolor and P. roqueforti was significantly inhibited by cell-free supernatants of all D. hansenii strains. The underlying factors behind the inhibitory effects of the D. hansenii cell-free supernatants were investigated. Based on dynamic headspace sampling followed by gas chromatography-mass spectrometry (DHS-GC-MS), 71 volatile compounds (VOCs) produced by the D. hansenii strains were identified, including 6 acids, 22 alcohols, 15 aldehydes, 3 benzene derivatives, 8 esters, 3 heterocyclic compounds, 12 ketones, and 2 phenols. Among the 71 identified VOCs, inhibition of germination of C. inversicolor correlated strongly with three VOCs, i.e. 3-methylbutanoic acid, 2-pentanone as well as acetic acid. For P. roqueforti, two VOCs correlated with inhibition of germination, i.e. acetone and 2-phenylethanol, of which the latter also correlated strongly with inhibition of mycelium growth. Low half-maximal inhibitory concentrations (IC50) were especially observed for 3-methylbutanoic acid, i.e. 6.32-9.53 × 10-5 and 2.00-2.67 × 10-4 mol/L for C. inversicolor and P. roqueforti, respectively. For 2‐phenylethanol, a well-known quorum sensing molecule, the IC50 was 1.99-7.49 × 10-3 and 1.73-3.45 × 10-3 mol/L for C. inversicolor and P. roqueforti, respectively. For acetic acid, the IC50 was 1.35-2.47 × 10-3 and 1.19-2.80 × 10-3 mol/L for C. inversicolor and P. roqueforti, respectively. Finally, relative weak inhibition was observed for 2-pentanone and acetone. The current study shows that native strains of D. hansenii isolated from Danish brines have antagonistic effects against specific contaminating molds and points to the development of D. hansenii strains as bioprotective cultures, targeting cheese brines and cheese surfaces.